Planning a system of permanent sample plots for integrated long-term studies of community-based forest management - Meilby, H; Puri, L; Christensen, M; Rayamajhi, S (Banko Janakari, 2023)
To monitor the development of four community-managed forests, networks of permanent sample plots were established in 2005 at sites in Chitwan, Kaski and Mustang Districts, Nepal. This research note documents the procedures used when preparing for establishment of the plot networks, evaluates the applied stratification of the forest on the basis of data gathered in pilot surveys conducted in the early 2005, and provides a discussion on the implications of the choices made.Key words: Community-managed forests; permanent sample plots; stratification; allocation; estimatesBanko Janakari Vol.16(2) 2006 pp.3-11